2010
DOI: 10.1002/marc.200900605
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinyl phosphonic acid): Hydrodynamic Properties and SEC‐Calibration in Aqueous Solution

Abstract: Poly(vinyl phosphonic acid) (PVPA) as obtained by free radical polymerization of aqueous vinyl phosphonic acid was studied by light scattering (SLS, DLS) and size exclusion chromatography (SEC) in dilute aqueous solutions containing sufficient salt in order to screen long range electrostatic interactions. Samples of 37<$\overline M _{\rm w}$< 110 × 10(3) were studied. The polymers showed positive A(2) -values in aqueous NaH(2) PO(4) solution (0.04 M), and self-diffusion behavior and R(H) /R(G) -ratios indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 28 publications
0
12
1
Order By: Relevance
“…For the latter, PVPA was completely desorbed from the collagen matrix after 24 h. Although cross-linking of collagen with EDC for 1 min only was not as effective to cross-linking of PVPA for 5 min, the extent of desorption PVPA from cross-linked collagen following a 5-min application of EDC was similar to a 4–24 h application of the cross-linking agent [18]. Conventionally, carbodiimides are used to cross-link collagen molecules by activating the carboxylic acid groups of glutamic or aspartic acid residues to react with amine groups of another chain, forming amide bonds [35]. As a member of the zero-length class of cross-linkers, EDC does not remain in the chemical bond but is released as a substituted urea molecule [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the latter, PVPA was completely desorbed from the collagen matrix after 24 h. Although cross-linking of collagen with EDC for 1 min only was not as effective to cross-linking of PVPA for 5 min, the extent of desorption PVPA from cross-linked collagen following a 5-min application of EDC was similar to a 4–24 h application of the cross-linking agent [18]. Conventionally, carbodiimides are used to cross-link collagen molecules by activating the carboxylic acid groups of glutamic or aspartic acid residues to react with amine groups of another chain, forming amide bonds [35]. As a member of the zero-length class of cross-linkers, EDC does not remain in the chemical bond but is released as a substituted urea molecule [36].…”
Section: Discussionmentioning
confidence: 99%
“…As a member of the zero-length class of cross-linkers, EDC does not remain in the chemical bond but is released as a substituted urea molecule [36]. However, cross-linking of collagen matrix by EDC to cause increases in its stiffness requires 4–6 h and the presence of N-hydroxysuccinimide to be effective [3538]. Moreover, the thiopeptolide employed in the MMP assay has the structure Ac-Pro-Leu-Gly-SCH[CH 2 CH(CH 3 ) 2 ]CO-Leu-Gly-OC 2 H 5 [39], which does not contain free carboxylic acid groups to enable intramolecular cross-links to be developed.…”
Section: Discussionmentioning
confidence: 99%
“…12 It has been only recently that free-radical polymerisation of VPA started to be studied in detail by several research groups. [13][14][15][16][17][18] The reactivity of chain transfer agents like thiols, disulfides and polyhalogenated compounds in VPA polymerisation was explored. 13,14 Among all the tested compounds, only perfluorohexyl iodide C 6 F 13 I 13 and bromotrichloromethane CCl 3 Br 14 led to VPA telomers of controlled lengths.…”
mentioning
confidence: 99%
“…Similar M n values were obtained when the phosphate buffer used as eluent for SEC was replaced with a 0.1 M NaNO 3 aqueous solution. 16 In contrast, under similar polymerisation conditions, Bing€ ol et al 15 reported the synthesis of high molecular weight PVPA (M w z 6 Â 10 4 g mol À1 ). This strong difference in obtained molar masses remains unclear and is still being questioned in our group.…”
mentioning
confidence: 99%
“…Molecules smaller than 40 kDa are completely excluded while those smaller than 6 kDa can diffuse into all water compartments of a collagen fibril [27]. The average molecular size of PVPA reported by the manufacturer (24 kDa) is really a mixture of PVPA polymers that include some that are smaller and larger than 24 kDa [41]. The smaller molecules can enter the water compartments of collagen.…”
Section: Discussionmentioning
confidence: 99%